# On proving $P(A^c \cap B) = P(B) - P(A \cap B)$

This is embarrassing, but I am unable to prove that $P(A^c \cap B) = P(B) - P(A \cap B)$. Any pointers?

-
Hint: What is $(A^c \cap B) \cap (A \cap B)$? What is $A^c \cup A$? Moving the $P(A \cap B)$ term to the other side may make things seem clearer. – cardinal Dec 10 '11 at 16:53
I'd have posted an answer, but "cardinal"'s comment says essentially what I would have said. – Michael Hardy Dec 10 '11 at 16:57
A different viewpoint (but basically the same thing as the above comments): Do you know that $B=(A^c\cap B) \cup (A\cap B)$ and the set $(A^c\cap B)$ and $(A\cap B)$ are disjoint? What do you know about probability of union of disjoint events? – Martin Sleziak Dec 10 '11 at 16:58
@MichaelHardy: You (or others) should feel free to post an answer. Cheers. :) – cardinal Dec 10 '11 at 17:03
@PKR: For future reference in asking homework questions, many users will generally want to see some attempt at a solution or more developed reasoning explaining why and where you are stuck. There is a helpful homework FAQ that I'd encourage you to read over. Cheers. – cardinal Dec 10 '11 at 17:18

What you want to show is equivalent to:

$$P(A^c \cap B) + P(A \cap B) = P(B)$$

Note by definition $(A^c \cap A)=\emptyset \Rightarrow (A^c \cap B) \cap (A \cap B) = \emptyset$

Besides you know that $(A^c \cap B) \cup (A \cap B)=B$

Therefore the statement follows by using the $\sigma$-additivity of $P$, namely

$$(X \cap Y)=\emptyset \Rightarrow P(X \cup Y)=P(X)+P(Y)$$

I let you write out the last step.

-